Allocation of the costs of transmission losses - Lima, D. A.; Padilha-Feltrin, A. (Elsevier B.V., 2004)
An analysis of the performance of six major methods of loss allocation for generators and demands was conducted, based on pro-rata (two), on incremental factors (two), on proportional sharing (PS) (one), and on electric circuit theory (one). Using relatively simple examples which can easily be checked, the advantages and disadvantages of each were ascertained and the results confirmed using a larger sample system (IEEE-118). The discussion considers the location and size of generators and demands, as well as the merits of the location of these agents for each configuration based on an analysis of the effect of various network modifications. Furthermore, an application in the South-Southeastern Brazilian Systems is performed. Conclusions and recommendations are presented. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: loss allocation; energy market; transmission networks; power flow